A study looking at changes in scores over time when using the Childhood Atopic Dermatitis Impact Scale. (3rd February 2020) - Gabes, M.; Chamlin, S.L.; Lai, J.‐S.; Cella, D.; Mancini, A.J.; Apfelbacher, C.J.
Summary: Atopic dermatitis is a common skin disease that causes extreme itching (called pruritus) and which mainly affects children. In the United States (U.S.A.), around 17% of schoolchildren are thought to have experienced atopic dermatitis and in Northern Europe, it is similar at about 16%. The researchers of this study are based in the U.S.A and in Germany. The Childhood Atopic Dermatitis Impact Scale (CADIS) is a questionnaire that measures quality of life in young children affected by atopic dermatitis, and their parents. This study aimed to find out whether the CADIS is able to detect changes over time and how big those changes have to be in order to be beneficial for the patients. Parents of affected children completed the CADIS and rated their child's skin condition on a single question at initial enrolment and four weeks later. Only children whose skin condition improved, showed significantly better CADIS scores after four weeks, i.e. the CADIS was sensitive to change towards improvement. However, change scores must be interpretable to be clinically useful. For this reason, the authors calculated the minimal important change (MIC), which is the smallest change in score which patients perceive as beneficial. An improvement in the CADIS of more than 12% was found to very likely represent a clinically important change. Since the CADIS is able to measure change over time, it is a useful instrument in clinical practice. This summary relates to the study: Evaluation of responsiveness and estimation of smallest detectable change and minimal important change scores for the Childhood Atopic Dermatitis Impact Scale Abstract : Linked Article:  Gabes et al. Br J Dermatol 2020; 182 :348–354